The Concept of Maqasid al-Shariah As an Instruments of Ijtihad According to Imam al-Shatibi in al-Muwafaqat fi Ushuli Al-Shariah - Al Ikhlas Al Ikhlas; Desi Yusdian; Alfurqan Alfurqan; Murniyetti Murniyetti; Nurjanah Nurjanah (Media Syari'ah, 2021)
As written in al-Muwafaqat fi Ushuli al-Syari'ah, Imam al-Shatibi explained that every divine law (the command of Allah) must be prescribed on purposes. The intended purposes or objective of the law is to fulfill for the benefit of humankind. Imam al-Shatibi divided the higher objectives of law into two categories: (1) the objectives of the Lawgiver (Allah), and (2) the human objectives (the benefits that refer to humankind as the doer of law). The human objectives are defined in three scales: from the ‘essential’ (dharûriyat), to the ‘necessary’ (hajiyât), and to the ‘complementary’ (tahsiniyât). Furthermore, Imam Al-Shatibi explained that there are four steps in understanding the human objectives. The first is understanding maqasid (objectives) through the purity of the command and prohibitions. The second is understanding maqasid through the existence of ‘illah (basis) contained in commands and prohibitions. And the third, understanding the maqasid through the law that related to 'adah (customs) and 'ibadah (worship) which have the main and additional objectives. Fourth, understanding the maqasid through silence on the part of Allah due to the absence of any occasions or circumstances for further declaration related to certain matter. In other word, there is no evidence from the Holy book on certain issue which provides the reasons of the law implementation despite the existence of the meaning (ma’na) behind the revelation.